1995
DOI: 10.1021/np50119a020
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Phorbol Ester from Excoecaria agallocha

Abstract: The novel phorbol ester 12-deoxyphorbol 13-(3E,5E-decadienoate) [1] was isolated as the anti-HIV principle of Excoecaria agallocha leaves and stems collected in northwest Australia. The structure was determined by spectral means. Compound 1 was also a potent displacer of [3H]-phorbol dibutyrate from rat brain membranes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 8 publications
(9 reference statements)
4
44
0
2
Order By: Relevance
“…12-Deoxyphorbol 13-decadienoate, isolated from Excoecaria agallocha as an anti-HIV principle, was also a potent displacer of [ 3 H]-phorbol dibutyrate from rat brain membrane. 32) However, other derivatives (4, 6) were found to potently inhibit the HIV-1-induced CPE without activating PKC. Kubinski et al 33) reported that although chemically related compounds tend to change the properties of the microsomal membrane in a similar way, TPA (8) decreased the amount of bound DNA 5-fold, while phorbol 12,13-didecanoate, the second strongest promoter, increased this amount by about one-third.…”
Section: Discussionmentioning
confidence: 99%
“…12-Deoxyphorbol 13-decadienoate, isolated from Excoecaria agallocha as an anti-HIV principle, was also a potent displacer of [ 3 H]-phorbol dibutyrate from rat brain membrane. 32) However, other derivatives (4, 6) were found to potently inhibit the HIV-1-induced CPE without activating PKC. Kubinski et al 33) reported that although chemically related compounds tend to change the properties of the microsomal membrane in a similar way, TPA (8) decreased the amount of bound DNA 5-fold, while phorbol 12,13-didecanoate, the second strongest promoter, increased this amount by about one-third.…”
Section: Discussionmentioning
confidence: 99%
“…The boundless tropical variety Excoecaria is known for the generation of dangerous metabolites [1]. It is appropriated on sea-shores and edge mangroves once in a while developed for wind and ocean softens up tropical Africa and east Asia.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical trials carried out on this plant showed its potential as anti-HIV, anticancer, antibacterial and antiviral agent (Peter et al, 1999). Previous phytochemical studies on E. agallocha revealed the presence of diterpenoids (ISI database, 2008;Ji-Dong et al, 2007;Li et al, 2007;Wang et al, 2006Kang et al, 2005), triterpenoids (Zou et al, 2006), fl avonoid (Konishi et al, 2003) and phorbole esters (Ericson et al, 1995). As part of our continuing phytochemical and bioactivity studies on Bangladeshi medicinal plants and also in other parts of the world (Alam et al, 2008a,b;Ali et al, 2008;Datta et al, 2007Datta et al, , 2004Saha et al, 2007;Uddin et al, 2007aUddin et al, -c, 2006aUddin et al, ,b, 2005Uddin et al, , 2004Rouf et al, 2006;Haque et al, 2004;Rahman et al, 2004;Delazar et al, 2006;Shoeb et al, 2007;Auzi et al, 2007;Zamani et al, 2007;Razavi et al, 2008), we now report on the neuropharmacological and antibacterial activities, and acute toxicty of the ethanol extract of the bark of E. agallocha in laboratory rodents as well as brine shrimp toxicity.…”
Section: Introductionmentioning
confidence: 99%